Pharmacological models in Alzheimer's disease research - Gilles, Christian (Les Laboratoires Servier, 2000)
Wider use of pharmacological models would facilitate the development of new drugs for Alzheimer's disease (AD), The two main models currently used are based on the cholinergic and glutamatergic hypotheses of AD, Although they lead to some of the attention and memory impairment observed in AD, they do not fully reproduce the AD pattern. The few studies that used a combination modeling approach, ie, the simultaneous administration of several drugs with the aim of impairing several neurotransmitters or different aspects of a single system, have reported no or marginal cumulative effect. On the basis of current understanding of glutamate and acetylcholine involvement in AD pathophysiology, we suggest that models using selective muscarinic-1 (M(1)) receptor blockers would better mimic the status of the cholinergic system in AD, This kind of model might be suitable for the assessment of drugs that do not act directly on the cholinergic system.